Common European Mitochondrial Haplogroups in the Risk for Radiation-induced Subcutaneous Fibrosis in Breast Cancer Patients. Issue 6 (June 2016) - Terrazzino, S.; Deantonio, L.; Cargnin, S.; Donis, L.; Pisani, C.; Masini, L.; Gambaro, G.; Canonico, P.L.; Genazzani, A.A.; Krengli, M.
Abstract: Aims: The contribution of mitochondrial DNA (mtDNA) variations to clinical radiosensitivity is largely unknown. In the present study, we evaluated the association between mtDNA haplogroups and the risk of radiation-induced subcutaneous fibrosis after postoperative radiotherapy in breast cancer patients. Materials and methods: Subcutaneous fibrosis was scored according to the Late Effects of Normal Tissue-Subjective Objective Management Analytical (LENT-SOMA) scale in 286 Italian breast cancer patients who received radiotherapy after breast-conserving surgery. Eight mtDNA single nucleotide polymorphisms that define the nine major haplogroups in the European population were determined by polymerase chain reaction restriction fragment length polymorphism analysis on genomic DNA extracted from peripheral blood. Results: In a Kaplan–Meier analysis evaluated by the Log-rank test, carriers of haplogroup H were found to be at lower risk of grade ≥2 subcutaneous fibrosis ( P  = 0.018) compared with all other haplotypes combined. In the multivariate Cox regression analysis adjusted for clinical factors (body mass index, breast diameter, adjuvant treatment, dose per fraction, radiation type and acute skin toxicity), haplogroup H emerged as a protective factor for moderate to severe radiation-induced fibrosis at a nominal significance level (hazard ratio: 0.50, 95% confidence interval 0.27–0.92, P  = 0.027), which did not survive correction for multiple testing. Conclusions: Our results suggest a protective effect of the mitochondrial haplogroup H in the development of radiation-induced fibrosis in breast cancer patients. However, the loss of statistical significance after correction for multiple comparisons and the lack of an independent validation cohort make our findings preliminary, requiring further confirmation in large-scale prospective studies. Highlights: Risk of radiation-induced skin fibrosis was assessed using mitochondrial DNA haplogroups. A protective role was found of mitochondrial haplogroup H in breast cancer patients. This effect was mainly due to a higher risk conferred by haplogroups U and J.